2009
DOI: 10.1186/1471-2180-9-188
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane porin M35 of Moraxella catarrhalis mediates susceptibility to aminopenicillins

Abstract: BackgroundThe outer membrane protein M35 is a conserved porin of type 1 strains of the respiratory pathogen Moraxella catarrhalis. It was previously shown that M35 is involved in the uptake of essential nutrients required for bacterial growth and for nasal colonization in mice. The aim of this study was (i) to characterize the potential roles of M35 in the host-pathogen interactions considering the known multifunctionality of porins and (ii) to characterize the degree of conservation in the phylogenetic older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…in more than 90% of clinical isolates. 2 One study reported a significant increase in MIC for ampicillin and amoxicillin in M35 porin-deficient mutants, 24 which suggests that this porin affects outer membrane permeability for aminopenicillins in a clinically relevant manner.…”
Section: Disscussionmentioning
confidence: 99%
“…in more than 90% of clinical isolates. 2 One study reported a significant increase in MIC for ampicillin and amoxicillin in M35 porin-deficient mutants, 24 which suggests that this porin affects outer membrane permeability for aminopenicillins in a clinically relevant manner.…”
Section: Disscussionmentioning
confidence: 99%
“…20 We studied 52 middle ear isolates obtained from Prof. Ron Dagan (Beer-Sheva, Israel). PCR resulted in positive products for all 52 strains.…”
Section: Resultsmentioning
confidence: 99%
“…20 To verify these findings in vivo and clarify its clinical relevance regarding amoxicillin therapy of acute otitis media caused by M. catarrhalis , further analyses will be needed. In particular, it will be necessary to elucidate whether down-regulation of M35 during treatment may contribute to treatment failure caused by isolates that have been shown to be susceptible in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The Opp system of M. catarrhalis is essential for mediating uptake of peptides between 5 and 10 aa residues in length, yet peptides of smaller or larger size were not dependent on the Opp system for uptake. We speculate that smaller and larger peptides are being imported by other mechanisms, such as the general porin complex in the case of small peptides or through an uptake system that has not yet been characterized (58). An alternative explanation for the larger peptides is that they may undergo proteolytic degradation in the periplasm by any number of annotated peptidase enzymes present in the genome of M. catarrhalis that have not been characterized (38,59,60).…”
Section: Discussionmentioning
confidence: 99%